Market orientation, entrepreneurship orientation, relationship commitment and communication among SME exporters in Malaysia - Md Daud Ismail,; Azwardi Md Isa,; Syed Shah Alam,; Maisarah Ahmad, (School of Social, Development and Environmental Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2016)
Building partnerships with foreign importers or distributors is critical for internationalizing small and medium enterprises with limited resources. Doing so can help them leverage the resources of their partners and enhance their export performance in foreign markets. Within this context, commitment to the relationship stands as an important cross-border relationship dimension. In addition, market orientation and entrepreneurship orientation have been highlighted in the literature as important variables to develop relationship commitment. The literature also demonstrates that effective communication between partners is the critical function of relationship closeness and strength. This study used the resource-based view for theoretical foundation. We collected data from 220 small and medium business exporters in the manufacturing sector in an emerging market, namely, Malaysia which were analyzed using hierarchical moderated regression analysis. The results showed that entrepreneurship orientation is positively related to relationship commitment. The findings also revealed that the relationship between market orientation and commitment was fully moderated by communication. This means the entrepreneurial values of risk taking, innovation, and pro-action are crucial in providing SMEs with the ability to develop and maintain relationship commitment. Future studies may investigate how the rapid changes in the international business environment affect SME relationship commitment.